Dimensional Accuracy Control and Compressive Property of Microcellular Polyetherimide Honeycomb Foams Manufactured by an In Situ Foaming Fused Deposition Modeling Technology. Issue 7 (19th March 2021) - Zhai, Wentao; Hu, Bin; Li, Mengya; Jiang, Junjie; Zhou, Mengnan
Abstract : The microcellular honeycomb foams can be manufactured via fused deposition modeling (FDM) technology. However, the process often involves complicated pre/post‐treatment. Herein, a novel in situ foaming FDM technology is developed to efficiently fabricate the microcellular polyetherimide (PEI) honeycomb foams with various lattice structures. The extremely low gas diffusivity endows the CO2 ‐saturated PEI filament with a long‐time printing ability and well printing performance, which is characterized by a long printable time up to 7 days and the formation of microcellular structure within the deposited foam strands. The printed PEI foam parts possess high dimensional accuracy with a relative accuracy ( δ R ) of 1.3–6.4% at the external regions and low internal accuracy with δ R of 27.5–48.8%, resulting from the increased nozzle expansion and reduced melt viscosity. An accuracy correction based on the nozzle expansion is effective to improve the dimensional accuracy of the foam parts. The high accuracy control of macro/microstructure and the advantages of green processing and long‐time printing make the in situ foaming FDM technology show great application prospects in the fabrication of hierarchical cellular materials. Abstract : A novel in situ foaming fused deposition modeling technology is developed to fabricate microcellular polyetherimide honeycomb foams. Low gas diffusivity endows the CO2 ‐saturated PEI filament with a long‐time printing ability and excellent printing performance. An accuracy correction based on the nozzle expansion is effective to improve the internal dimensional accuracy of the foam parts.